Manajemen Konflik di Lembaga dan Organisasi: Analisis Tren, Kategori, dan Strategi Penyelesaian - Lelly Anggraini; Roifatul Hasanah; Mayaza Rizqi Amelia; Ifrotul Hasanah; Mu’alimin Mu’alimin (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
Conflict is an inevitable phenomenon in organizational life and has the potential to greatly affect performance, interpersonal relationships, and institutional sustainability. The complexity of interactions in educational, business, and social environments makes this issue increasingly relevant for in-depth study. This study aims to examine the development of scientific studies on types of conflict and conflict management strategies over the past six years. The main focus of the study is to answer two questions: what types of conflict are most dominant in organizations, and how are conflict resolution strategies applied in various institutional contexts? The research method used is a literature review with the main keyword “types of conflict,” through searches in several scientific databases. From the selection results, five relevant articles were obtained and then analyzed based on research themes and trends. The analysis results show three main findings. First, conflicts within organizations can be classified into intrapersonal, interpersonal, and intergroup conflicts. Second, conflict resolution strategies emphasize the importance of effective communication, collaboration, mediation, and participatory leadership in creating sustainable solutions. Third, ethical and religious dimensions are also important aspects in building fair and harmonious resolutions. This study confirms that effective conflict management requires a multidimensional approach that integrates managerial, psychological, and moral values. Researchers are encouraged to conduct comparative studies between institutions to enrich their understanding of organizational conflict dynamics.